2014
DOI: 10.18311/jade/2014/2427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eruption of Third Molar Tooth among South Indians and Malaysians

Abstract: <strong>Introduction:</strong>In prehistoric humans, when the jaw size permitted space for normal dental development and position in the arches, third molar may have been a vital survival tool. However, as human evolution has progressed, jaw size has been gradually decreasing (Lamarckian Evolution). Hence due to the decrease in size of the jaw bone, it’s been reported that approximately 65% of the human population has at least one impacted third molar, and third molars that do erupt are often malpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Some mutations have been shown to cause agenesis, but there are currently no known mutations that cause agenesis without other symptoms. While studies have long suggested a genetic component to agenesis (Garn and Lewis 1962;Shimizu et al 2013), environmental disturbances occurring before the M3 initiates have been shown to produce this pathology (Swee et al 2013 Odds ratio of female to male M3 agenesis Bansal, 2012Sandhu and Kaur, 2005Byahatti et al, 2011Ren and Kumar, 2014Shah and Parekh, 2014Garcia−Hernandez and Rodriguez, 2009Nicodemo, 1973Bhowmik, 2013Daito et al, 1992Hellman, 1936Haga et al, 2013Golovcencu and Geletu, 2012Shah and Boyd, 1979Lee et al, 2009Bhutta and Sadozai, 2013Hubenthal, 1989Sonnabend, 1966Raloti et al, 2013Nanda and Chawla, 1959Kirveskari et al, 1978Ghada, 2005Weise and Bruntsch, 1965Sarmiento and Herrera, 2004Garcia−Hernandez et al, 2008Elomaa and Elomaa, 1973Costa et al, 2007Godt and Greve, 1980Celikoglu and Kamak, 2012Celikoglu et al, 2010Krekeler et al, 1974Haga et al, 2013Speckin, 1981Hentisz, 2003Shinn, 1976Oliveira and Serra Negra, 1984Oliveira and Serra Negra, 1976Mok and Ho, 1996Afify and Zawawi, 2012Holzl, 1972Endo et al, 2015Kazanci et al, 2010Thompson et al, 1974Adler and Adler−Hradecky, 1963…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some mutations have been shown to cause agenesis, but there are currently no known mutations that cause agenesis without other symptoms. While studies have long suggested a genetic component to agenesis (Garn and Lewis 1962;Shimizu et al 2013), environmental disturbances occurring before the M3 initiates have been shown to produce this pathology (Swee et al 2013 Odds ratio of female to male M3 agenesis Bansal, 2012Sandhu and Kaur, 2005Byahatti et al, 2011Ren and Kumar, 2014Shah and Parekh, 2014Garcia−Hernandez and Rodriguez, 2009Nicodemo, 1973Bhowmik, 2013Daito et al, 1992Hellman, 1936Haga et al, 2013Golovcencu and Geletu, 2012Shah and Boyd, 1979Lee et al, 2009Bhutta and Sadozai, 2013Hubenthal, 1989Sonnabend, 1966Raloti et al, 2013Nanda and Chawla, 1959Kirveskari et al, 1978Ghada, 2005Weise and Bruntsch, 1965Sarmiento and Herrera, 2004Garcia−Hernandez et al, 2008Elomaa and Elomaa, 1973Costa et al, 2007Godt and Greve, 1980Celikoglu and Kamak, 2012Celikoglu et al, 2010Krekeler et al, 1974Haga et al, 2013Speckin, 1981Hentisz, 2003Shinn, 1976Oliveira and Serra Negra, 1984Oliveira and Serra Negra, 1976Mok and Ho, 1996Afify and Zawawi, 2012Holzl, 1972Endo et al, 2015Kazanci et al, 2010Thompson et al, 1974Adler and Adler−Hradecky, 1963…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between M3 agenesis and impaction remains unexplored. Bansal, 2012Sandhu and Kaur, 2005Byahatti et al, 2011Ren and Kumar, 2014Shah and Parekh, 2014Garcia−Hernandez and Rodriguez, 2009Nicodemo, 1973Bhowmik, 2013Daito et al, 1992Hellman, 1936Haga et al, 2013Golovcencu and Geletu, 2012Shah and Boyd, 1979Lee et al, 2009Bhutta and Sadozai, 2013Hubenthal, 1989Sonnabend, 1966Raloti et al, 2013Nanda and Chawla, 1959Kirveskari et al, 1978Ghada, 2005Weise and Bruntsch, 1965Sarmiento and Herrera, 2004Garcia−Hernandez et al, 2008Elomaa and Elomaa, 1973Costa et al, 2007Godt and Greve, 1980Celikoglu and Kamak, 2012Celikoglu et al, 2010Krekeler et al, 1974Haga et al, 2013Speckin, 1981Hentisz, 2003Shinn, 1976Oliveira and Serra Negra, 1984Oliveira and Serra Negra, 1976Mok and Ho, 1996Afify and Zawawi, 2012Holzl, 1972Endo et al, 2015Kazanci et al, 2010Thompson et al, 1974Adler and Adler−Hradecky, 1963Grahnen, 1956Sandhu and Kapila, 1982Garcia−Hernandez and Beltran, 2008Haavikko, 1971Castilho et al, 1990Gravely, 1965Alam et al, 2014M...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on a relatively small sample size of 150 individuals, a prevalence rate of only 5.4% was reported [29]. On the contrary, another study on 50 individuals showed a prevalence rate of 56% [30]. A study involving a study population of 1005 showed a prevalence of mandibular M3 agenesis of 12%.…”
Section: Discussionmentioning
confidence: 91%
“…Clinical accounts of third molar agenesis in Asia appear to be higher than most European groups: 30% in a Malaysian Malay population (Alam et al, 2014), 33% in a Chinese Malaysian population (Alam et al, 2014), 50% in Nepal (Upadhyaya et al, 2012), 32.3% in Japan (Endo et al, 2015) and 38.4% in Bangladesh (Sujon et al, 1984). Ren & Kumar (2014) also report a prevalence of agenesis of 48% of males and 64% of females from southern India, but only 25 individuals of each sex were analyzed, and therefore the small sample size may not be representative.…”
Section: Discussionmentioning
confidence: 99%